2014
DOI: 10.3389/fendo.2014.00066
|View full text |Cite
|
Sign up to set email alerts
|

GPER Function in Breast Cancer: An Overview

Abstract: The G-protein-coupled estrogen receptor-1 (GPER, formerly known as GPR30) has attracted increasing interest, considering its ability to mediate estrogenic signaling in different cell types, including the hormone-sensitive tumors like breast cancer. As observed for other GPCR-mediated responses, the activation of the epidermal growth factor receptor is a fundamental integration point in the biological action triggered by GPER. A wide number of natural and synthetic compounds, including estrogens and anti-estrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 88 publications
0
77
0
3
Order By: Relevance
“…In addition, our and other studies have largely demonstrated the involvement of GPER in the stimulatory effects elicited by estrogens in cancer cells and tumor microenvironment (6,(9)(10)(11). Significantly, several studies performed in different cell and animal models have ascertained the role exerted by GPER in certain pathological conditions characterized by oxygen deficiency (30,31,(74)(75)(76)(77)(78).…”
Section: Gper Is Involved In Hypoxia-mediated Signalingmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, our and other studies have largely demonstrated the involvement of GPER in the stimulatory effects elicited by estrogens in cancer cells and tumor microenvironment (6,(9)(10)(11). Significantly, several studies performed in different cell and animal models have ascertained the role exerted by GPER in certain pathological conditions characterized by oxygen deficiency (30,31,(74)(75)(76)(77)(78).…”
Section: Gper Is Involved In Hypoxia-mediated Signalingmentioning
confidence: 90%
“…Consequently, the pharmacological manipulation of certain GPCR-mediated signaling may represent a promising anti-cancer strategy (3,4). As demonstrated for many GPCRs (3,4), the G protein estrogen receptor (GPER, also known as GPR30) may trigger oncogenic signaling (5,6). GPER binds to estrogens, phyto-and xenoestrogens, and also estrogen receptor (ER) antagonists that may act as GPER agonists (7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…GPER provides further potential complexity for molecular subtyping as a means to assign therapy since steroidal and nonsteroidal ER antagonists (tamoxifen, fulvestrant and raloxifene) have been demonstrated to function as GPER agonists [Filardo, 2011;Petrie et al, 2013;Lappano et al, 2014;Prossnitz and Barton, 2014]. Interestingly, large comparative clinical studies indicate that blockade of estrogen biosynthesis by use of aromatase inhibitors (AIs) has benefit over blockade of the nuclear estrogen receptors as a strategy for treating ER-positive breast cancer.…”
Section: Gper Role In Breast Cancermentioning
confidence: 99%
“…However, as described above, estrogens, as well as other steroids, had also been demonstrated to mediate rapid cellular and physiologic responses, inconsistent with the time frame of transcriptional mechanisms (Falkenstein et al, 2000). The discovery and characterization of a third estrogen receptor in the 2000s (Filardo et al, 2000;Revankar et al, 2005;Thomas et al, 2005), namely GPR30/GPER, belonging to the family of 7-transmembrane G proteincoupled receptors (GPCRs), which classically mediate rapid responses such as kinase activation and ion mobilization, have expanded our understanding of the varied and complex activities of estrogenic compounds throughout the body (Prossnitz, , 2012Prossnitz and Barton, 2009, 2014Prossnitz and Maggiolini, 2009b;Filardo and Thomas, 2012;Han et al, 2013;Srivastava and Evans, 2013;Lappano et al, 2014;Barton and Prossnitz, 2015).…”
Section: Introductionmentioning
confidence: 99%